A Model for Increasing the Efficiency of Teaching Physics in High Schools with the Help of Cloud Technologies - Toyir's daughter, Usmonova Sahiba (International Journal on Integrated Education, 2023)
This article presents the possibilities, methods of use of modern educational technologies in the development of the competences of high school students in physics, and the model of developing the skills of students to independently complete the tasks given in theoretical, practical, laboratory, and group classes during the lesson and outside of the lesson. Experiments were also carried out in order to determine the level of efficiency of the proposed model. The results obtained in the experiment were analyzed using the chi-square test.